2022
DOI: 10.1186/s12889-022-13822-5
|View full text |Cite
|
Sign up to set email alerts
|

Household-level sanitation in Ethiopia and its influencing factors: a systematic review

Abstract: Background Within the past two decades, Ethiopia has achieved one of the fastest reductions of open defecation worldwide. This change can be attributed to the implementation of a national sanitation strategy that focused on facilitating community demand for latrine adoption and use of basic self-constructed latrines but less on other preconditions of hygienic sanitation. Recognition of sanitation by policymakers also catalyzed primary research in this area. As such, the synthesis of the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…In addition to the results obtained in this study, the lower latrine coverage among lower SES households has been shown in previous studies [ 30 , 40 ]. The low latrine coverage among people with low incomes could be explained in terms of the cost of latrine construction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition to the results obtained in this study, the lower latrine coverage among lower SES households has been shown in previous studies [ 30 , 40 ]. The low latrine coverage among people with low incomes could be explained in terms of the cost of latrine construction.…”
Section: Discussionsupporting
confidence: 87%
“…More so, the cost of constructing a public latrine in a community can be funded by external or co-financing, whereas self-financing is generally required for the individual latrines of households based on CLTS policy [ 13 ]. Thus, whereas several studies have indicated that individual beliefs about cost and benefit are predictors of latrine ownership [ 25 , 30 ], the issue of motivation plays an important role. It can be assumed that there are differences in motivation between households depending on their SES, in as much as CLTS tries to motivate the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prominent approach within this strategy was the Ethiopian adaptation of Community-Led Total Sanitation and Hygiene, building upon the Community-Led Total Sanitation (CLTS) approach ( Crocker et al ., 2017 ; Novotný et al, 2018a ). However, the increased latrine coverage often compromised quality, using low-cost, locally available materials, resulting in sustainability issues, collapses, and a resurgence of open defecation ( Abebe and Tucho, 2020 ; UNICEF, 2020 ; Novotný and Mamo, 2022 ; Kouassi et al ., 2023 ). Research indicates that relying solely on the CLTS approach may not be sufficient for achieving hygienic sanitation ( Cavill et al , 2015 ; Crocker et al ., 2017 ; Novotný et al, 2018b ; Ficek and Novotný, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Novotný and Mamo ( 2022 ) reviewed the factors affecting household-level sanitation in Ethiopia, highlighting that key focus has been on understanding the adoption of basic latrines; and studies on identifying the drivers of the sustainability of sanitation such as upgrading of latrines, has been rare despite its urgency. Rashid and Pandit ( 2019 ) analyzed the issue of lack of disposal systems among household toilets and found that the households are willing to pay for better service quality and improvement in attributes of toilets and hygiene.…”
Section: Introductionmentioning
confidence: 99%